Visualizing the Growth and Division of Rat Gut Bacteria by D-Amino Acid-Based in vivo Labeling and FISH Staining - Chen, Ru; Song, Jia; Lin, Liyuan; Liu, Jie; Yang, Chaoyong; Wang, Wei (Frontiers in Molecular Biosciences, 2021)
Rat is a widely used mammalian model for gut microbiota research. However, due to the difficulties of individual in vitro culture of many of the gut bacteria, much information about the microbial behaviors in the rat gut remains largely unknown. Here, to characterize the in situ growth and division of rat gut bacteria, we apply a chemical strategy that integrates the use of sequential tagging with D-amino acid-based metabolic probes (STAMP) with fluorescence in situ hybridization (FISH) to rat gut microbiota. Following sequential gavages of two different fluorescent D-amino acid probes to rats, the resulting dually labeled gut bacteria provides chronological information of their in situ cell wall synthesis. After taxonomical labeling with FISH probes, most of which are newly designed in this study, we successfully identify the growth patterns of 15 bacterial species, including two that have not been cultured separately in the laboratory. Furthermore, using our labeling protocol, we record Butyrivibrio fibrisolvens cells growing at different growth stages of a complete cell division cycle, which offers a new scope for understanding basic microbial activities in the gut of mammalian hosts.